Microsoft Certified Azure Data Fundamentals (DP-900) Exam Guide Build a solid foundation in Azure data services and pass the DP-900 exam on your first try - Miles, Steve; Miles, Steve (Packt Publishing, 2024)
Boost your Azure career by mastering essential data concepts and cloud services with this pragmatic guide Purchase of this book unlocks access to web-based exam prep resources such as mock exams, flashcards, exam tips, and the eBook PDFKey FeaturesGain Azure certification insights from industry veteran and Microsoft MVP, Steve MilesDive into expertly crafted content aligned with the latest DP-900 exam requirementsTest your skills with mock exams that mirror the actual certification examBook DescriptionMicrosoft's Azure Data Fundamentals (DP-900) certification exam validates your expertise in core data concepts and Azure$1 (Bs powerful data services capabilities. This comprehensive guide written by Steve Miles$1 (Ba Microsoft Azure MVP and certified trainer with over 25 years of experience in cloud data services and 30+ certifications across major platforms$1 (Bserves as your gateway to a future shaped by data and AI, regardless of your technical background. With the help of examples, you'll learn fundamental data concepts, including data representation, data storage options, and common workloads and gain clarity on the roles and responsibilities of key data professionals such as data administrators, engineers, and analysts. This guide covers all crucial exam domains, from data services capabilities of the Azure cloud platform to considerations for relational, non-relational, and analytics workloads, encompassing both Microsoft and open-source technologies. To supplement your exam prep, this book gives you access to a suite of online resources designed to boost your confidence, including mock tests, interactive flashcards, and invaluable exam tips By the end of this book, you$1 (Bll be fully prepared not only to pass the DP-900 exam but also to confidently tackle data solutions in Azure, setting a strong foundation for your data-driven careerWhat you will learnAnalyze features of structured, semi-structured, and unstructured dataUtilize Azure SQL and open-source database services confidentlyIdentify and evaluate Azure storage optionsUnderstand the versatility of Azure Cosmos DB through use cases and APIsApply cutting-edge strategies for large-scale analytics in AzureMaster core data concepts crucial for Azure environmentsExplore Microsoft's cloud services for real-time analyticsDemonstrate proficiency in data visualization using Power BIWho this book is forThis exam guide is designed for anyone who wants to work with Azure data services and prepare for the Azure DP-900 exam. Whether you're an administrator, engineer, architect, developer, analyst, aspiring data scientist, or a non-technical enthusiast interested in learning data concepts, this book is for you. It also lays the groundwork for those planning to pursue more advanced data or AI certifications. A foundational understanding of cloud concepts and client-server applications is assumed.s